PERAN BRAND IMAGE MEMEDIASI PERCEIVED QUALITY DAN SOCIAL MEDIA TERHADAP PURCHASE INTENTION - Winadi Prasetyoning Tyas, Ari Anggarani; Billyyando, Billy (Institut Bisnis Nusantara, 2025)
In the midst of intense competition in the fashion industry, companies are required to understand factors influencing consumer purchase intention. Brand image is not formed directly but is influenced by perceived quality and social media marketing. This study aims to determine the effect of perceived quality and social media marketing on purchase intention with brand image as a mediating variable in the fashion industry. The study uses a quantitative approach by distributing questionnaires to 110 prospective Uniqlo buyers in Bekasi, referring to Hair's minimum sample rule (number of statements x 5). Data analysis uses Structural Equation Modeling Partial Least Square (SEM-PLS). Results show that perceived quality does not form brand image but directly drives purchase interest through rational evaluation of product quality. Social media marketing effectively builds brand image through visual content and digital interaction, but does not directly trigger purchases because young consumers are more critical of promotions. Brand image becomes a strong driving factor for purchase intention through emotional connections and social identity. Brand image mediates the influence of social media marketing on purchase intention, but does not mediate the perceived quality-purchase intention relationship. Perceived quality and social media marketing have different influence paths. Fashion companies need to develop integrated strategies that combine direct product quality communication with brand image building through social media.